How do they like it? Higher education teachers’ professional development preferences for blended learning and technology acceptance profiles - Anja Garone; Sarah K. Howard; Jie Yang; Jo Tondeur; Bram Pynoo; Bram Bruggeman; Katrien Struyven (Computers in Human Behavior Reports)
Blended learning is useful in higher education for catering to diverse student learning needs, however, higher education teaching staff need to be trained and supported so that it is applied attentively. Higher education teachers are diverse themselves with complex professional development needs. This study aims to examine the relationships between professional development preferences and 217 teaching staff grouped into technology acceptance profiles: high, moderate and low. Association rules analysis was run on an 18-item questionnaire dataset of the teaching staff's professional development preferences for blended learning. Results show that the high group is highly motivated to professionalise themselves collaboratively with added central support. The moderate group prefers centrally organised and guided professional development initiatives. The low group prefers centrally organised initiatives with guidance as well as incentive for professionalisation. These results highlight the differences between the groups, and how these preferences can be useful for designing targeted initiatives along with adapted communication strategies for groups with different technology acceptance levels.